The effect of tobacco leaf extract dosage on the development of virus disease in curly chili - Priyadi, Sapto; Haryuni , Haryuni (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Curly chili is a horticultural product with high nutritional value, greatly demanded as a distinctive complement or flavoring for dishes due to its unique taste and aroma. Despite the increasing demand for chilies, production has not followed suit, mainly due to disruption caused by viruses transmitted by Bemisia tabaci and Thrips sp. This study aimed to investigate the effect of tobacco extract on the growth and development of viral diseases in curly chili. Conducted at Kwangsang Village, Jumapolo District, Karanganyar Regency, from September to December 2021, the research was designed using a completely randomized block design, with treatment doses of tobacco extract at 0 mL/L, 1 mL/L, 2 mL/L, 3 mL/L, and 4 mL/L, labeled J0, J1, J2, J3, and J4, respectively. The results indicated that the variabels, i.e. plant height, number of leaves, number of fruits, and fruit weight per plant, were significantly affected by the tobacco extract. Similarly, the disease incidence and severity of viral infection were significantly influenced by the tobacco extract application. The yield decrease in curly chili was attributed to virus infection by Bemisia tabaci and Thrips sp., which caused chlorosis and mosaic symptoms on the leaves. Although the affected plants did not die, they experienced a yield reduction. The application of tobacco extract significantly reduced the percentage of incidence and severityof virus infection on curly chili. The highest disease incidence was 35.42% (J0) and disease severity was 70.92% (J0), while the lowest disease incidence was 14.58% (J4) and disease severity was 20.58% (J4).